Does the use of betahistine dihydrochloride affect positional nystagmus? - Aslan, Beyza; Demirhan, Hasan; Yasak, İlknur; Yiğit, Özgür; Bayazıt, Yıldırım Ahmet (Hayat Health and Social Services Foundation, 2022)
Aim: In this study, we aimed to investigate the effect of betahistine dihydrochloride (BD) use on positional nystagmus as an objective criterion for the diagnosis of benign paroxysmal positional vertigo (BPPV). Methods: The retrospective study included 59 patients (15 males, 44 females) who were aged between 18 and 80 years and referred with suspected BPPV to the otorhinolaryngology clinic of the Istanbul Training and Research Hospital. Only patients who had no central pathology on oculomotor tests were included. Of the patients included, those not using BD were classified as Group I and those using BD medication (24 mg/day) within the last 48 hours as Group II. The positional nystagmus latency, duration, and slow-phase velocity (SPV) values were compared using videonystagmography. Results: There was no significant difference between the two groups in terms of oculomotor gains (p>0.05). While there was no difference between the two groups in terms of positional nystagmus latency and SPV values, nystagmus duration was found to be significantly longer in Group II. Conclusion: Although the BD use appears to prolong the duration of nystagmus in BPPV, it does not affect the other parameters of nystagmus, including SPV, and the prolonged duration is still within normal limits. Positional nystagmus can be investigated in patients with a history of suspected BPPV and BD prescription.

Amaç: Bu çalışmada betahistin dihidroklorür (BD) kullanımının benign paroksismal pozisyonel vertigo (BPPV) tanısında objektif kriter olan pozisyonel nistagmus üzerine etkisini incelemek amaçlanmıştır. Yöntem: Retrospektif çalışmamız yaşları 18–80 yıl aralığında değişen ve BPPV şüphesiyle İstanbul Eğitim ve Araştırma Hastanesi’nin kulak–burun–boğaz polikliniğine yönlendirilen 59 (15 erkek, 44 kadın) hasta içerdi. Çalışmaya yalnızca okülomotor testlerde santral patoloji görülmeyen hastalar dahil edildi. Dahil edilen hastalardan BD kullanmayanlar Grup I, son 48 saat içinde BD grubu ilaç (24 mg/gün) kullananlar ise Grup II olarak tasnif edildi. Pozisyonel nistagmus latans, süre ve yavaş faz hızı (YFH) değerleri videonistagmografi kullanılarak karşılaştırıldı. Bulgular: İki grup arasında okülomotor kazançlar bakımından anlamlı bir fark bulunmadı (p>0,05). Yine iki grup arasında pozisyonel nistagmus latans ve YFH değerleri açısından fark saptanmazken nistagmus süresi Grup II’de anlamlı olarak daha uzun bulundu. Sonuç: BD kullanımı BPPV’de pozisyonel nistagmus süresini uzatıyor gibi görünse de YFH dahil diğer nistagmus parametrelerini etkilememektedir ve süredeki uzama halen normal sınırlar içindedir. BPPV şüphesi ve BD reçeteleme öyküsü olan hastalarda pozisyonel nistagmus araştırılabilir.
Betahistin dihidroklorür kullanımı pozisyonel nistagmusu etkiler mi?
Keywords: Benign Paroxysmal Positional Vertigo; Betahistine; Nystagmus; Benign Paroksismal Pozisyonel Vertigo; Betahistin; Nistagmus